2013
DOI: 10.1111/1747-0080.12057
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the cost of a healthy food basket and fruit and vegetable availability in New South Wales, Australia, between 2006 and 2009

Abstract: Aim To compare food costs and variety of fresh fruits and vegetables (F&V) available at three time points in December 2006, December 2008 and July 2009. Methods Data on the cost of a 44‐item food basket across the main food groups including fresh and packaged foods were collected in 2006 (149 stores), 2008 (105 stores) and 2009 (129 stores). In addition, the number of varieties of 30 different fresh F&V was surveyed. Stores included the two major supermarket chains and smaller grocery chains using a convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 14 publications
1
34
2
Order By: Relevance
“…Although the present study found that being a general store was the strongest predictor of missing food items, urban or regional location also mattered. Research from other Australian states and territories have shown decreased healthy food availability in general stores or community stores and with increasing remoteness . We did not find a relationship between availability and location, when expressed as distance from the capital city CBD.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Although the present study found that being a general store was the strongest predictor of missing food items, urban or regional location also mattered. Research from other Australian states and territories have shown decreased healthy food availability in general stores or community stores and with increasing remoteness . We did not find a relationship between availability and location, when expressed as distance from the capital city CBD.…”
Section: Discussioncontrasting
confidence: 86%
“…To date, variations of a healthy food basket have been used in each state and territory to assess the cost, affordability and availability of a healthy diet. This food monitoring research has largely focused on food cost . Less is known about the physical availability of healthy food, with most research examining food availability from a socioeconomic perspective, often measuring fruit and vegetables only .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, resettled refugees have reported that the cost of vegetables is higher than that of meat, which may account for the increased consumption of meat and decreased consumption of fruits and vegetables reported among resettled refugees . In addition, the cost of core foods such as fruits and vegetables has also been reported to be high across Australia . As almost half of the participants were unemployed and more than half had annual household incomes below $30 000, they may not be able to afford to include healthy foods in their diets.…”
Section: Discussionmentioning
confidence: 99%
“…4,21 In addition, the cost of core foods such as fruits and vegetables has also been reported to be high across Australia. [22][23][24] As almost half of the participants were unemployed and more than half had annual household incomes below $30 000, they may not be able to afford to include healthy foods in their diets. Hence, by growing their own food, resettled refugees have an inexpensive way of accessing healthy foods such as vegetables, enabling them to make healthy food choices at little or no cost.…”
Section: Discussionmentioning
confidence: 99%